Improvement of mechanical properties in treated spot welded joint / Farizah Adliza Ghazali ... [et al.] - Ghazali, Farizah Adliza; Salleh, Zuraidah; HP Manurung, Yupiter; Md Taib, Yakub (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Post Weld Impact Treatment (PWIT) is one of the treatment method usually applied on weld region to reduce the level of residual stress originated from welding process. During the spot weld process, the formation of stress produced around the weld area and degrade the mechanical properties of the joint. This paper focused on the improvement of mechanical properties of spot welding joint via Pneumatic Impact Treatment (PIT) process. This experiment used the material of low-carbon steel with welded single lap shear joint with the constant thickness of 1.2 mm. All the welded samples were subjected to tensile-shear test, failure mode and hardness test. The tensile-shear load and fusion zone hardness of RSW joint after PIT was improved by 8% and 27%, respectively. The results indicated improvement in tensile-shear strength and hardness of treated samples compared to as-welded samples. From the observation, the failure mode was the failure mode type which was generally accepted failure for spot-weld joint. The improvements of the mechanical properties is envisaged as the result of the mechanical pulses produced by unique fluidic muscle conveyed to the surface of the RSW joint during PIT process.